Comparative Performance of Tree Species Suitable for Agroforestry System - Chandrasekharaiah, A M; Prabhakar, A S (Annals of Arid Zone, 2016)
A field experiment was conducted at Agricultural College, Dharwad, Karnataka, during kharif, 1979 through 1984 to evaluate the performance of six tree species (viz., Leucaena /eucocepha/a, eucalyptus, sissoo, casuarina, teak and bamboo) in agroforestry system, Eucalyptus produced significantly higher total harvestable biomass per plant (168.11 kg) than other species at the end of the fifth year after planting. This was followed by sisso, bamboo, casuarina and teak. Leucaena produced the minimum total harvestable biomass per plant (30.05 kg) co pared to other species.